Big data and predictive analytics capabilities : a review of literature on its impact on firm’s financial performance - Lee, Khai Loon; Lim, Cean Peing (KnE Social Sciences, 2019)
In the era of the fourth industrial revolution, big data and predictive analytics (BDPA) capabilities considered as one of the significant resources that enable a firm to gain competitiveness. Nowadays, the advancement of technology information increases the difficulty of the firm to manage vast amounts of structured and unstructured data. The excessive growth between data captured and the firm’s capabilities to manage, process, analyze, and transfer the big data to actionable knowledge and value still challenges many firms in the competitive market. Besides, the lack of tangible resources, technical skills, management skills, organizational learning, and data-driven culture are some of the challenges for firms to apply analytics approach to support the data processing process. These situations led to poor decision making by the firm and result in high operation cost and lower profitability. However, the situation will be different if the firm able to manage BDPA capabilities in the right way. Based on the identified problems, this study aims to review the impact of BDPA capabilities on a firm’s financial performance. This study is expected to enhance the body of knowledge on BDPA capabilities and the firm’s financial performance. This study also provides information regarding the importance of BDPA capabilities on the firm’s financial performance to industrial practitioners. An empirical study on this subject matter is suggested for future researchers, especially in Malaysia manufacturing industry.